Higiene dan Sanitasi pada Pedagang Angkringan di Kawasan Malioboro Yogyakarta - Dyah Suryani; Fardhiasih Dwi Astuti (Jurnal Kedokteran dan Kesehatan, 2019)
Foodborne disease more of the cases caused by poor food handling techniques, and contamination occurs when served. Food handler hygiene and sanitation are the key to be success in processing safe and healthy foods. Poor sanitation hygiene can be affect the quality of the food. It cause consumer health level who is consume these food. If the hygiene and sanitation of food bad it could result in health problems. Based on this background, the study are interested in knowing the factors related to sanitation hygiene in angkringan traders in the Malioboro area. This study was observasional analitic with cross sectional design. The study sample was angkringan traders in Malioboro area with 40 angkringan traders. Sampling technique with total sampling. The instruments used questionnaire and checklist sheets. Data analysis used univariate analysis and bivariate analysis with Fisher statistical test. The results of the study statistics test for 40 angkringan traders, showed that 32 traders had high knowledge (80%), 36 traders had a good attitude (90%), 29 traders had poor sanitation facilities (72.5%), 26 traders had bad hygiene sanitation (65%). There is no relationship between knowledge (p=0,222), attitude (p=1,000) with hygiene sanitation of traders. There is a relationship between sanitation facilities and hygiene sanitation traders (p=0,029).Keywords: Knowledge, attitude, sanitation facilities, hygiene, sanitation.